Role of nitrogen doping in modulating ruthenium nanocatalysts for enhanced electrochemical hydrogen evolution reaction in alkaline medium - Korampattu, Lavanya; Barik, Sidharth; Pandikassala, Ajmal; Urkude, Rajashri R.; Kurungot, Sreekumar; Dhepe, Paresh L. (Chemistry of Materials, 2024)
Nitrogen doping has become a fundamental approach to enhance the catalytic performance of carbon materials across various applications. The introduction of nitrogen creates defects and active sites, promoting the formation of small metal particles and strengthening the metal-support interaction within carbon materials. However, the challenge lies in developing sustainable and cost-effective methods for synthesizing nitrogen-doped carbon materials. In this study, we present a sustainable approach for the synthesis of ruthenium on nitrogen-doped carbon catalysts (Ru-CCP) using chitosan as a nitrogen and carbon source. Unlike traditional methods, our process avoids the use of additional nitrogen precursors and templates, streamlining the synthesis while using a renewable resource. The synthesized material exhibits an exceptional performance in the electrochemical hydrogen evolution reaction (HER) in alkaline conditions by achieving a current density of 25 mA cm(-2) at an impressively low overpotential of 46 mV, outperforming Pt/C under similar conditions. The detailed studies on structural and electronic properties of the materials using X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and transmission electron microscopy (TEM) revealed that the remarkable catalytic activity is upheld by the unique interplay between Ru delta+ and surface nitrogen moieties, notably pyridinic and pyrrolic nitrogen. Here, we demonstrate the control of particle size and electronic environment around the metal atom via the interaction of nitrogen and unravel the role of nitrogen doping in tuning the catalytic performance. In addition, this work offers insights into efficient HER catalyst design and emphasizes the potential of biomass-derived materials like chitosan in advancing clean hydrogen production for renewable energy applications.

Ru/MgO-catalysed selective aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Lokhande, Priya; Dhepe, Paresh L.; Wilson, Karen; Lee, Adam F. (Australian Journal of Chemistry - an International Journal for Chemical Science, 2024)
Biomass valorisation through the selective oxidation of carbohydrate and lipid derivatives offers access to an array of platform chemicals through energy- and atom-efficient catalytic processes. Supported metal nanoparticles are promising catalysts for the aerobic selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA), but typically require strong liquid base to achieve high selectivity. Here, we explore the utility of MgO as a solid base support for the Ru-catalysed aerobic oxidation of HMF, obtaining 68% FDCA yield at 160°C and 1.5 MPa of O<span style="box-sizing: inherit; font-size: 11.25px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(0, 49, 60); font-family: "Open Sans", sans-serif; background-color: rgb(241, 250, 244);">2 using <1 mol-% metal.